2010
DOI: 10.1016/j.biomaterials.2010.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of angiogenesis during osseointegration by titanium surface microstructure and energy

Abstract: Rough titanium (Ti) surface microarchitecture and high surface energy have been shown to increase osteoblast differentiation, and this response occurs through signaling via the α2β1 integrin. However, clinical success of implanted materials is dependent not only upon osseointegration but also on neovascularization in the peri-implant bone. Here we tested the hypothesis that Ti surface microtopography and energy interact via α2β1 signaling to regulate the expression of angiogenic growth factors. Primary human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
137
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 44 publications
8
137
0
2
Order By: Relevance
“…However, despite the success achieved through surface chemistry modifications in the early host-implant integration, there is a general consensus that the modulation of surface texturing is also an important and desirable variable, regardless of the surface chemistry approach followed in endosseous implants 18,19) . The benefits of topographical surface modifications have been previously described in vitro and in vivo [20][21][22][23] . In vitro studies have shown that surface topography affects different cellular functions such as cell adhesion, proliferation, differentiation and local factor production 24) , but that it also favours appropriate implant-cell interactions on the bone-implant interface [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the success achieved through surface chemistry modifications in the early host-implant integration, there is a general consensus that the modulation of surface texturing is also an important and desirable variable, regardless of the surface chemistry approach followed in endosseous implants 18,19) . The benefits of topographical surface modifications have been previously described in vitro and in vivo [20][21][22][23] . In vitro studies have shown that surface topography affects different cellular functions such as cell adhesion, proliferation, differentiation and local factor production 24) , but that it also favours appropriate implant-cell interactions on the bone-implant interface [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…At the micro-scale, in vitro studies have shown that surface roughness enhances osteoblast differentiation and stimulates the local production of both osteogenic (TGF) and angiogenic (VEGF, FGF, EGF) growth factors 41,42) . Moreover, in vivo studies have shown that a microrough titanium dental implant surface topography increases bone-to-implant contact and improves the clinical rate of wound healing 1) .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct contact between blood vessels and implant surface in osseointegrated implant, appropriate blood supply plays an important role in healing of both hard and soft tissues. Studies of the last years focus on investigating the role of angiogenesis and the interaction between angiogenesis and osteogenesis in wound healing after implantation [7][8][9] . Endothelial cells (ECs), which underlie the inner surface of the vasculature, play a key role in the angiogenesis, and therefore their interaction with titanium surfaces is an important factor influencing tissue healing.…”
Section: Introductionmentioning
confidence: 99%